2000
DOI: 10.1108/02630800010322508
|View full text |Cite
|
Sign up to set email alerts
|

A factor approach to the analysis of components’ defects in housing stock

Abstract: This paper seeks to explore and detect underlying relationships between identifiable primary causes of defects in local authority housing stock with the view to identifying which groups of building components are associated with one another. It is primarily based on responses to a questionnaire from building surveyors who were involved in the day-to-day diagnosis of defects of a large local authority housing stock. The intercorrelations among the primary defect-causing factors demanded the application of princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…It has been established among factor analysts, Tabachnick and Fidell (1989); Child (1990); Siegel and Castellan (1988) and in studies by Egbu (1994); Olubodun (1996; 2000) that the property of multicollinearity is highly undesirable for tests under factor analysis. In other ways the correlations between the owner and builder maintenance attributes should not be extremely high, as this undermines the use of factor technique to detecting common variance among the attributes.…”
Section: Collection and Analysis Of Survey Datamentioning
confidence: 99%
See 2 more Smart Citations
“…It has been established among factor analysts, Tabachnick and Fidell (1989); Child (1990); Siegel and Castellan (1988) and in studies by Egbu (1994); Olubodun (1996; 2000) that the property of multicollinearity is highly undesirable for tests under factor analysis. In other ways the correlations between the owner and builder maintenance attributes should not be extremely high, as this undermines the use of factor technique to detecting common variance among the attributes.…”
Section: Collection and Analysis Of Survey Datamentioning
confidence: 99%
“…Olubudun (2000) has cited Child (1990) as having described the essence of factor analysis as likely to benefit any field of research that aspires not only to describe, but also to generate from a given set of data, generalisations, inferences and predictions; to rely on the credence of factor analysis as a statistical tool. Overall and Klett (1972) considered factor analysis, as a reduction technique concerned with relationships among test variates and relationship of the test variates to derived factors.…”
Section: Statistical Technique For Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in England conducted by Olubodun (2000) on housing stock reveals the similar nature of problems in the housing stock under study. The survey revealed that various implicating factors of design faults and construction are present in housing of United Kingdom.…”
Section: Building Lifespanmentioning
confidence: 99%
“…Defective construction works can be defined as works that fall short of complying with the express descriptions or requirements of the contract. Accordingly Olubodun [23] states the majority of modern buildings and civil structures are complex and involve the use of a great variety of engineering methods and processes. Therefore, most projects face the possibility of defects and defective work, which generally result in structures that cannot perform their originally intended roles.…”
Section: Construction Defectsmentioning
confidence: 99%